DESIGN AND FORMULATION DEVELOPMENT OF FAST-DISSOLVING TABLETS OF IBUPROFEN USING NOVEL NATURAL SUPERDISINTEGRANT - CHANDRA SEKHAR NAIK D; BHARATHI A; BASAVESWARA RAO MV (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to evaluate Ocimum gratissimum mucilage as a novel superdisintegrant in the formulation of fast-dissolving tablets (FDT) of Biopharmaceutical Classification System-II drug (Ibuprofen) employing a 23 factorial design. Methods: O. gratissimum mucilage was extracted by seeds and it was subjected to physical, chemical, and micrometric studies were evaluated. To establish FDT of ibuprofen with O. gratissimum mucilage as a superdisintegrants in different ratios using direct compression method employing 23 factorial design. All the formulation tablets were evaluated pre-compression and post-compression parameters like dissolution efficiency (DE%) percent of drug dissolved at 5 min. Results: The mucilage was to be found fine, free-flowing crystalline powder, and excellent swelling nature in all suitable solvents and buffers. The Fourier transform infrared and differential scanning calorimetry studies were indicated to no interactions between ibuprofen and O. gratissimum mucilage. All the FDT formulated employing novel mucilage shows good quality with regard drug content (98.05±0.31–99.39±0.54), hardness (3.6– 4 kg/sq. cm), and friability (0.12–0.15%). The optimized formulation batch shows less disintegrant time (30±0.06). In vitro wetting time was less (i.e., 90 s) in optimized formulation F2. The water absorption ratio of the formulated tablets was found to be in the range of 99±0.56. The cumulative drug dissolved in the optimized formulation F2 was found to be 99% in 10 min. Conclusion: O. gratissimum mucilage was found to be a novel superdisintegrant which enhanced the DE when combined with crospovidone and croscarmellose sodium; hence, it could be used in the formulation of FDT to provide immediate release of the contained drug within 5 min.